2004
DOI: 10.1002/ejic.200300700
|View full text |Cite
|
Sign up to set email alerts
|

The Ligating Ability of Functionalised Diaminodimethylsilanes towards Zirconium(IV)

Abstract: have been synthesised by aminolysis of SiMe 2 Cl 2 with NH 2 (CH 2 ) n X, and their ligating ability towards zirconium(iv) has been investigated. L 4 ) are reported and the solid-state structures of some selected compounds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The aminosilanes Ph 2 Si(NHCH 2 CH 2 NMe 2 ) 2 ( 1 ), Me 2 Si(NHCH 2 CH 2 N i Pr 2 ) 2 ( 2 ) and Ph 2 Si(NHCH 2 CH 2 N i Pr 2 ) 2 ( 3 ) were prepared according to a procedure described by Passarelli et al for the synthesis of Me 2 Si(NHCH 2 CH 2 NMe 2 ) 2 7 [Equation (1)]. In the case of MeSi(NHCH 2 CH 2 N i Pr 2 ) 3 ( 4 ) MeSiCl 3 was treated with N , N ‐diisopropylethylenediamine and triethylamine as auxiliary base [Equation (2)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aminosilanes Ph 2 Si(NHCH 2 CH 2 NMe 2 ) 2 ( 1 ), Me 2 Si(NHCH 2 CH 2 N i Pr 2 ) 2 ( 2 ) and Ph 2 Si(NHCH 2 CH 2 N i Pr 2 ) 2 ( 3 ) were prepared according to a procedure described by Passarelli et al for the synthesis of Me 2 Si(NHCH 2 CH 2 NMe 2 ) 2 7 [Equation (1)]. In the case of MeSi(NHCH 2 CH 2 N i Pr 2 ) 3 ( 4 ) MeSiCl 3 was treated with N , N ‐diisopropylethylenediamine and triethylamine as auxiliary base [Equation (2)].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the use of functionalized silylamide ligands bearing additional donor groups has opened new perspectives in coordination chemistry in particular concerning the stabilization of transition metal dinitrogen complexes5 and lanthanoid metal alkyl complexes 6. In 2004 Passarelli et al reported on zirconium complexes with functionalized silylamide ligands of the type [Me 2 Si(NCH 2 CH 2 X) 2 ] 2– and [Me 2 Si(NCH 2 CH 2 CH 2 X) 2 ] 2– with X = NMe 2 or OMe 7. Crystal structure analyses of these compounds revealed that the functionalized silylamides behave as tetradentate ligands which coordinate through the amide function and the hetero atom of the X donor group.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from steric requirements, the coordination properties of silylamide ligands can be customized by the introduction of additional side arm donor functions. The first studies go back to 2004 when Passarelli et al synthesized functionalized silylamides [Me 2 Si(NCH 2 CH 2 X) 2 ] 2− (X = OR, NR 2 ) and applied them for the generation of zirconium polymerization catalysts [5]. Recently, we found that thioether-functionalized silylamides [Me 2 Si(N-C 6 H 4 -2-SR′) 2 ] 2− (R′ = Me, Ph) can be successfully used for the synthesis of Cu(I), Ag(I), Au(I), and Tl(I) complexes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The more complex pattern of the 2pyridyl group resonances is observed in the region between 7.96-6.45 ppm (3) and 8.00-6.12 ppm (5). In the case of the derivatives [{Ph 2 Si(N-2-py) 2 Sn} 2 ] (4) and [{Ph 2 Si(N-2py) 2 Pb} 2 ] (6) there is a partial overlap of the signals of the phenyl and the 2-pyridyl groups in the range 7.91-7.05 ppm (4) and 7.88-6.33 ppm (6). Regarding the 29 Si NMR spectra, ARTICLE the Me 2 Si derivatives 3 and 4 behave differently from the Ph 2 Si derivatives 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…As early as 2004 Passareli et al developed silylamide ligands of the type [Me 2 Si(NCH 2 CH 2 X) 2 ] 2-(X = OR, NR 2 ), which were successfully applied in the synthesis of novel Zr IV silylamides with intramolecular donor group stabilization. [6] Other approaches comprise the employment of more complex side-arms, which are suitable for simultaneous intramolecular M-N and M-P coordination. Using this structural pattern, several novel transition metal dinitrogen complexes were made accessible.…”
Section: Introductionmentioning
confidence: 99%